Health education teaching, interdisciplinarity and public health policies - doi:10.5020/18061230.2006.p182 - Maria Grasiela Teixeira Barroso; Neiva Francenely Cunha Vieira; Zulene Maria de Vasconcelos Varela (Universidade de Fortaleza, 2012)
The national curriculum directives of health area graduation courses and texts about interdisciplinary, health promotion/education and public policies framed the discussion about health education, which, in this context, is an area of political pedagogical knowledge, considering that its knowing and doing have been historically determined by social and economical conditions that guide public policies . This work aimed at motivating readers to open up psycho-pedagogical, cultural and operational scenery within an interdisciplinary approach towards human development and, as a consequence, to nourish the hope of contributing for the promotion of human beings' quality of life. We consider that this work offers a valuable contribution for the reflexion of educators and students committed to the empowerment of health policies. It is necessary that teachers and students have freedom to create and to learn how to teach in different sceneries and levels of care. It is a question of assuming a social and ethical commitment to reduce the distance between privileged and excluded people and to permeate professional life with an idea of "knowing and being", which includes the art of accepting the other, the learning of how to learn through reflexive, critical and continuous reexamination of the apprehended concepts in the world of information. After all, we conclude with an attitude based on the science domain, being linked to other areas that characterize human being identity as a transcendental dimension.